2016
DOI: 10.1161/circinterventions.115.002981
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into Timing, Risk Factors, and Outcomes of Stroke and Transient Ischemic Attack After Transcatheter Aortic Valve Replacement in the PARTNER Trial (Placement of Aortic Transcatheter Valves)

Abstract: T ranscatheter aortic valve replacement (TAVR) has revolutionized management of elderly patients with severe aortic stenosis, 1,2 but post-TAVR neurological events remain a concern for patients and physicians. Although occurrence of post-TAVR stroke has fallen from ≈5% in initial trials to 3% in recent reports, reducing this risk is essential for advancing this technology into lower-risk patient cohorts. See Editorial by Dangas and GiustinoUnderstanding the mechanisms of neurological events is critical for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
113
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(121 citation statements)
references
References 32 publications
(27 reference statements)
5
113
3
Order By: Relevance
“…Post‐hoc data from the PARTNER trial and other observational and meta‐analytical studies have shown new‐onset AF to be associated with greater risk for cerebrovascular events at 30 days. However, despite the anticipated adverse effects of AF, we did not observe statistically significant differences in 30‐day risk of outcomes compared with patients in sinus rhythm in this study.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Post‐hoc data from the PARTNER trial and other observational and meta‐analytical studies have shown new‐onset AF to be associated with greater risk for cerebrovascular events at 30 days. However, despite the anticipated adverse effects of AF, we did not observe statistically significant differences in 30‐day risk of outcomes compared with patients in sinus rhythm in this study.…”
Section: Discussioncontrasting
confidence: 80%
“…The pathophysiology of new‐onset AF post TAVR has been linked with increased left atrial stress from LV dysfunction, and local inflammatory processes from the TAVR procedure inciting ectopic atrial activity . However, the most important risk factor for new‐onset AF is TAVR access, with significantly greater risk from nontransfemoral (non‐TF) approaches . This is hypothesized to be due to nonpercutaneous surgical access, postoperative access site pain and complications including infection triggering inflammatory pathways .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have correlated RVP with a clinical end point. A sub‐analysis of the PARTNER trial found that in the subgroup of patients undergoing transapical TAVR, a greater number of pacing runs (not pacing duration) showed intermediate association with higher risk for stroke 3. Similarly, a report from the CoreValve trials indicated a higher risk of stroke in patients who underwent RVP for predilation of the aortic valve versus those who did not 8.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prior case reports and small‐scale studies have reported conflicting data on the hemodynamic effects and clinical impact of RVP during TAVR 1, 2, 3, 4. Thus the aim of the present study was to assess the clinical impact of RVP on immediate and long‐term outcomes in a large cohort of non‐selected TAVR patients.…”
Section: Introductionmentioning
confidence: 97%
“…Given it was splinting the mitral valve apparatus, there was concern about potential damage to the valve upon removal in addition to arterial embolization. The risk of embolic stroke during interventions within the arterial system is well described within the transcatheter aortic valve implantation (TAVI) cohort of patients; there is a high prevalence of subclinical infarcts on neurological imaging and clinical cerebrovascular accidents 8. There are, however, no published reports of transcutaneous extraction of endocardial LV leads, and therefore, the prevalence of such complications is unknown.…”
Section: Discussionmentioning
confidence: 99%